Teaching at the Right Level Approach for Autistic Children in Islamic Religious Education in Inclusive Classrooms - Yunita, Ita; Ilma, Labibah Sayaka; Saidah, Anis; Asrohah, Hanun; Zainiyati, Husniyatus Salamah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2025)
The purpose of this study is to analyze the extent to which the TaRL approach can be adapted in PAI learning practices that are responsive to the unique needs of children on the autism spectrum. This study uses a qualitative method with a field research design. Data were collected through direct observation of learning activities in inclusive classes, in-depth interviews with PAI teachers, special assistant teachers (GPK), and parents of autistic students, and analysis of learning documents. The results show that the TaRL approach, which emphasizes learning based on students' actual ability levels, can be implemented effectively through differentiated instructional strategies, the use of visual media based on religious values, and collaborative support between teachers, parents, and the school environment.